Understanding mucosal responsiveness: lessons from enteric bacterial pathogens - Simmons, Cameron (2018)
Mucosal immune responses must discriminate between commensal flora within the lumen and potential pathogens. These responses are highly adapted to induce protection without excessive inflammation. The balances that regulate mucosal immune and inflammatory responses have to be understood if effective mucosal immunity is to be induced through local immunization. This review will summarize some of the lessons learnt from studies of antigens derived from enteric bacterial pathogens and discuss how the gastrointestinal epithelia can 'fight back' when it encounters pathogens.